Medicinal Plant Use by Traditional Healers in the Muaro Jambi Temple Complex - Helman Kurniadi; Aminuddin Aminuddin; Fitria Heldiana (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Traditional medicinal knowledge plays an essential role in community health practices, yet much of it remains undocumented and at risk of being lost. This study investigated the ethnobotanical knowledge of traditional healers in the cultural landscape surrounding Candi Muaro Jambi, Indonesia. From April to July 2025, interviews were conducted with seven key informants recognized for their expertise in traditional healing. Information on plant names, parts used, preparation methods, routes of application, and treated ailments was collected and verified through botanical identification. A total of 98 medicinal plant species were documented, with leaves most frequently used (45.9%), followed by fruits, stems, seeds, bark, or latex (30.6%), and roots, rhizomes, or tubers (23.5%). Boiling was the predominant preparation method, valued for its simplicity and effectiveness in extracting water-soluble compounds. The recorded remedies addressed a wide spectrum of health conditions, including infections, inflammatory diseases, metabolic disorders, and respiratory problems, applied both orally and topically. These findings highlight the cultural importance and pharmacological potential of local ethnomedicinal practices, providing a valuable foundation for future drug discovery and biodiversity conservation.